Stereospecific and selective enzymatic resolution of carboxylic acid derivatives in organic solvents - Elazar, Meyer (Technium BioChemMed, 2023)
Enzymes such as lipases and proteases have been used as catalysts in nearly anhydrous organic solvents such as diisopropyl ether and hexane to carry out stereospecific and selective enzymatic resolutions of carboxylic acid derivatives such as 2-bromohexadecanoic acid, which may be used for prevention and treatment of bone loss-related diseases and β-phenyllactic acid, which has a role as a human metabolite.